Unravelling the Yamaji Imaginings of Alexander Morton and Daisy Bates - Barrington, Robin (ANU Press, 2015)
In the late nineteenth and early twentieth centuries, Alexander Morton and Daisy Bates deployed the photograph as a privileged evidentiary anthropological document. Their photographic representations of Yamaji from Western Australia circulated within a transnational network of discourses and practices involving anthropologists, police, pastoralists and journalists, and served to cement views of Yamaji as racially homogeneous, primitive and uncivilised. This article explores the histories behind these photographs and their polysemy to challenge some of the scientific and popular 'truths' disseminated about their Yamaji subjects. It discusses how Yamaji as figures of Aboriginalist discourse were represented in the work of two influential public figures, Alexander Morton and Daisy Bates, and through their interactions within scientific and colonial networks of power.